Gender on the screen: a public point of view of private writing (2008)
Abstract: This paper examines the public and private nature of personal weblogs written by British and Spanish teenagers. In particular, it reports on the first stage of a long-term research project about the effects of the anti-sexist language policies and the process of feminisation of the language in the media. Given that the linguistic expression of online female gender identity includes a wide range of variables, I shall concentrate on a selection of pragmatic meanings of informative and directive utterances in British and Spanish female teenagers’ narrations of their love-life. In doing so, I shall highlight the fight between the persistence of traditional patriarchal feminine behaviours and the growing appearance of culturallybased androgynous behaviour patterns in both British and Spanish societies.